أثر جودة الحياة الوظيفية على سلوك المواطنة التنظيمية - منيرة, عروك (University of eloued جامعة الوادي, 2020)
"نهدف من خلال هذه الدراسة إلى التعرف على أثر جودة الحياة الوظيفية على سلوك المواطنة التنظيمية، حيث تم استخدام الاستبيان لجمع البيانات من (143) مستجيب من الموظفين العاملين بالمؤسسة روائح الورود بالوادي. ومن أهم النتائج التي تم الوصول إليها، أن جودة الحياة الوظيفية وسلوك المواطنة التنظيمية سائدان وسط الموظفين بالمؤسسة، وأن هناك علاقة طردية بين جودة الحياة الوظيفية وسلوك المواطنة التنظيمية."" We aim through this study to identify the impact of the quality of work life on the behavior of organizational citizenship, where the questionnaire was used to collect data from (143) respondents from the employees working in the institution smells of roses in the valley. Among the most important results that have been reached, is that the quality of career life and organizational citizenship behavior prevail among the employees of the institution, and that there is a direct relationship between the quality of job life and organizational citizenship behavior. "
مذكرة ماستر ادارة اعمال
Keywords: جودة الحياة الوظيفية، سلوك المواطنة التنظيمية، مؤسسة ورود ، معامل الارتباط; Quality of work life, organizational citizenship behavior, Woroud institution, correlation coefficient